Use PEMDAS.
Parenthesis first.
(-15)-(-12)+3-(-9)
Next multiply,
(-15)+12+3+9 (two negatives get you a positive)
Finally, add and subtract:
-15+24=9
You get 9 as your answer.
Hope this helps!
Answer:
2/5
Step-by-step explanation:
The answer is " 768 square feet. ".
Total surface area of a triangular prism = width x height +(sum of sides + width) x length and here;
width = 10
height = 12
sides = 13
length = 18
= (10 x 12) + (13 + 13 + 10) x 18
= 120 + (36 x 18)
= 120 + 648
= 768 square feet.
Answer:
(-3, 4).
Step-by-step explanation:
When f(x) becomes f(x + 1), all that is happening is that the y-value increases by 1.
So, (-3, 3) becomes (-3, 3 + 1). That is (-3, 4).
Hope this helps!
F(g(x)) = f(3x+2) = h(x)=9x^2+12x + 6
Note that (3x+2)^2 = 9x^2 + 12x + 4, which is almost, but not quite, equal to h(x).
Let's experiment. What if f(x) = x^2 + 2?
Then f(3x+2) = (3x+2)^2 + 2 = 9x^2 + 12x + 4 + 2 = 9x^2 + 12x + 6, which is the same as the given h(x).
Thus, f(x) is x^2 + 2.